Self-repairing corrosion-resistant coating and preparation method thereof

By forming a combined coating of self-healing graphene and nano-silica gel on the surface of magnesium alloy, the problem of corrosion of magnesium alloy in humid environment is solved, high corrosion resistance and self-healing performance are achieved, and the coating life is extended. longevity and reduced maintenance costs.

CN119350969AInactive Publication Date: 2025-01-24DONGGUAN MUNICIPAL RONGDA HARDWARE PRODUCTS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411241658.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Magnesium alloys corrode faster in humid natural environments, and it is difficult for the prior art to effectively improve their corrosion resistance and self-repair capabilities.

Method used

Self-healing graphene is formed by grafting silicon-oxygen bonds on the surface of graphene and introducing disulfide bonds through D-cystine esterification modification; then using triethoxysilyl undecaldehyde and dodecyltrimethoxy The hydrolytic polymerization of silane-based silane forms nano-silica gel, which is combined with self-healing graphene to improve the corrosion resistance and self-healing performance of the coating.

Benefits of technology

It significantly improves the corrosion resistance and self-healing performance of the magnesium alloy surface, extends the service life of the coating, reduces maintenance costs, and isolates the penetration of corrosive liquids through long hydrophobic chains, thereby enhancing the anti-corrosion ability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005029471390000051
    Figure BDA0005029471390000051
Patent Text Reader

Abstract

The invention discloses a self-repairing corrosion-resistant coating and a preparation method thereof, and relates to the technical field of coatings. Graphene is modified by N-(3-triethoxysilylpropyl)-4-hydroxybutyramide and D-cystine to form self-repairing graphene, and a disulfide bond is introduced into a molecular chain of the coating, so that the self-repairing effect of the coating is improved; then, gel is formed through hydrolytic polymerization of triethoxysilyl undecanal and dodecyltrimethoxysilane, side chains are combined with self-repairing graphene through chemical bonds, the crosslinking density is improved, micropores and defects in a coating are sealed, the corrosion resistance of the coating is improved, and then by means of the viscosity of the gel, the corrosion resistance of the coating is improved. The coating prepared by the method can be better combined on the alloy surface, the corrosion resistance and self-repairing performance of the coating are exerted to the greatest extent, the service life of the coating is greatly prolonged, the maintenance cost is reduced, and meanwhile, hydrophobic long chains carried by the organic silicon gel can isolate corrosive liquid from permeating to a certain extent, so that the corrosion resistance of the coating is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a self-repairing corrosion-resistant coating and a preparation method thereof. Background Art

[0002] Due to its light weight, high strength-to-weight ratio, good electromagnetic radiation isolation, easy casting and high content in the earth's crust, magnesium alloys have gradually been used in the shell materials of household appliances including mobile phones, laptops, tablets, lamps, etc. Since magnesium alloys are in a more active position in the electromotive force sequence and potential sequence, magnesium alloys corrode faster in the natural environment, especially in a humid environment. Therefore, surface treatment is an indispensable process in the production of magnesium alloy products. At present, there are many methods on the market to increase the corrosion resistance of magnesium alloys, such as powder coating, paint spraying, micro-arc oxidation followed by electrophoresis, etc.

[0003] Although the direction of magnesium alloy surface treatment in the past decade has mainly focused on improving its corrosion resistance, recently there have been a number of magnesium alloy surface treatments for decorative purposes or with multiple special functions that have become research and development hotspots. Among these magnesium alloy surface coatings with special functions, self-healing coatings are very attractive to designers and manufacturers. Summary of the invention

[0004] The purpose of the present invention is to provide a self-repairing corrosion-resistant coating and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a self-repairing corrosion-resistant coating, comprising the following preparation steps:

[0006] (1) adjusting the pH of the graphene dispersion to 2-5 with hydrochloric acid, adding a coupling agent solution, ultrasonically reacting at 60° C. for 8-20 h, filtering, taking out the solid, repeatedly washing with deionized water until the pH value is neutral, and then drying at 80° C. for 24 h to obtain pretreated graphene;

[0007] (2) mixing 10 parts by weight of D-cystine, 4 to 7 parts by weight of pretreated graphene, 0.01 to 0.05 parts by weight of methanesulfonic acid, and 20 to 30 parts by weight of N,N-dimethylformamide, heating the mixture under nitrogen protection for reaction, then cooling the mixture to room temperature, filtering the filtrate, and drying the mixture to obtain modified graphene;

[0008] (3) triethoxysilyl undecylaldehyde, dodecyltrimethoxysilane, modified graphene, anhydrous ethanol, and deionized water were mixed, stirred at 100 rpm for 8 to 12 minutes, the pH value was adjusted to 8 with ammonia water, the stirring was continued for 3 to 4 hours, and the mixture was allowed to stand for 8 to 12 hours to obtain a wet gel;

[0009] (4) The magnesium alloy is placed in the wet gel, pulled, and then immersed in ethanol for 24 hours, taken out, and dried at 100° C. for 2 to 3 hours. The above steps are repeated 2 to 3 times to obtain a self-repairing corrosion-resistant coating.

[0010] Furthermore, the concentration of the graphene dispersion in step (1) is 1 to 4 wt%.

[0011] Furthermore, in step (1), the volume ratio of the graphene dispersion to the coupling agent solution is 90-99:1-10.

[0012] Furthermore, in the coupling agent solution of step (1), the volume ratio of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide, anhydrous ethanol and deionized water is 15-30:40-70:15-30.

[0013] Furthermore, the ultrasound in step (1) is 20 to 35 kHz.

[0014] Furthermore, the heating reaction in step (2) has a reaction temperature of 120 to 150° C. and a reaction time of 7 to 10 hours.

[0015] Furthermore, the drying in step (2) is carried out at a temperature of 80° C. and for 24 hours.

[0016] Furthermore, in step (3), the mass ratio of triethoxysilyl undecanealdehyde, dodecyltrimethoxysilane, modified graphene, anhydrous ethanol and deionized water is 1:0.5-1.0:0.05-0.1:6-10:1-3.

[0017] Furthermore, the pulling speed in step (4) is 1 cm / min.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The present invention utilizes the silicon oxygen bond of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide to be grafted on the graphene surface, and then esterifies it through D-cystine to introduce disulfide bonds to form self-repairing graphene, thereby indirectly improving the self-repairing effect of the coating; then triethoxysilyl undecanealdehyde and dodecyltrimethoxysilane are hydrolyzed and polymerized to form a nano-silica polymer gel, and the aldehyde group of the side chain is chemically bonded with the amino group of the self-repairing graphene to increase the crosslinking density, play a role in sealing the micropores and defects in the coating, and improve the coating. The gel has good corrosion resistance and then relies on its own viscosity to bond to the alloy surface. The amide and disulfide bonds in the gel molecular chain structure contain nitrogen, oxygen, sulfur and other electronegative atoms. They contain lone pairs of electrons and can form coordination bonds to the alloy surface for adsorption. They can better combine with the alloy surface to maximize the corrosion resistance and self-healing properties of the coating, greatly extending the service life of the coating and reducing maintenance costs. At the same time, the long hydrophobic chains carried by the silicone gel can isolate the penetration of corrosive liquids to a certain extent, thereby enhancing the corrosion resistance of the coating. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] (1) ultrasonically dispersing graphene oxide in water to obtain a graphene dispersion with a concentration of 1 wt%, adjusting the pH to 3.5 with hydrochloric acid, adding a coupling agent solution until the volume ratio of the graphene dispersion to the coupling agent solution is 90:1, ultrasonically reacting at 30 kHz and 60° C. for 12 h, filtering, taking the solid, repeatedly washing with deionized water until the pH value is neutral, and then drying at 80° C. for 24 h to obtain pretreated graphene; the volume ratio of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide, anhydrous ethanol, and deionized water in the coupling agent solution is 15:40:15;

[0023] (2) 10 parts by mass of D-cystine, 4 parts by mass of pretreated graphene, 0.01 parts by mass of methanesulfonic acid, and 28 parts by mass of N,N-dimethylformamide were mixed, heated to 135° C. under nitrogen protection, reacted for 7 hours, cooled to room temperature, filtered, and dried at 80° C. for 24 hours to obtain modified graphene;

[0024] (3) triethoxysilyl undecanealdehyde, dodecyltrimethoxysilane, modified graphene, anhydrous ethanol, and deionized water were mixed in a mass ratio of 1:0.5:0.05:10:2, stirred at 100 rpm for 8 min, adjusted the pH value to 8 with ammonia water, continued stirring for 3 h, and allowed to stand for 8 h to obtain a wet gel;

[0025] (4) The magnesium alloy was placed in the wet gel, pulled at a speed of 1 cm / min, and then immersed in ethanol for 24 h. The alloy was taken out and dried at 100 °C for 2 h. The above steps were repeated twice to obtain a self-repairing corrosion-resistant coating.

[0026] Example 2

[0027] (1) ultrasonically dispersing graphene oxide in water to obtain a graphene dispersion with a concentration of 2.5 wt%, adjusting the pH to 3.5 with hydrochloric acid, adding a coupling agent solution until the volume ratio of the graphene dispersion to the coupling agent solution is 94:6, ultrasonically reacting at 30 kHz and 60° C. for 14 h, filtering, taking the solid, repeatedly washing with deionized water until the pH value is neutral, and then drying at 80° C. for 24 h to obtain pretreated graphene; the volume ratio of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide, anhydrous ethanol, and deionized water in the coupling agent solution is 22:55:21;

[0028] (2) 10 parts by mass of D-cystine, 6 parts by mass of pretreated graphene, 0.01 parts by mass of methanesulfonic acid, and 25 parts by mass of N,N-dimethylformamide were mixed, heated to 135° C. under nitrogen protection, reacted for 7 hours, cooled to room temperature, filtered, and dried at 80° C. for 24 hours to obtain modified graphene;

[0029] (3) triethoxysilyl undecanealdehyde, dodecyltrimethoxysilane, modified graphene, anhydrous ethanol, and deionized water were mixed in a mass ratio of 1:0.7:0.08:8:2, stirred at 100 rpm for 10 min, adjusted the pH value to 8 with ammonia water, continued stirring for 3 h, and allowed to stand for 10 h to obtain a wet gel;

[0030] (4) The magnesium alloy was placed in the wet gel, pulled at a speed of 1 cm / min, and then immersed in ethanol for 24 h. The alloy was taken out and dried at 100 °C for 2 h. The above steps were repeated twice to obtain a self-repairing corrosion-resistant coating.

[0031] Example 3

[0032] (1) ultrasonically dispersing graphene oxide in water to obtain a graphene dispersion with a concentration of 4 wt%, adjusting the pH to 5 with hydrochloric acid, adding a coupling agent solution until the volume ratio of the graphene dispersion to the coupling agent solution is 99:10, ultrasonically reacting at 30 kHz and 60° C. for 20 h, filtering, taking the solid, repeatedly washing with deionized water until the pH value is neutral, and then drying at 80° C. for 24 h to obtain pretreated graphene; the volume ratio of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide, anhydrous ethanol, and deionized water in the coupling agent solution is 30:70:30;

[0033] (2) 10 parts by mass of D-cystine, 7 parts by mass of pretreated graphene, 0.05 parts by mass of methanesulfonic acid, and 30 parts by mass of N,N-dimethylformamide were mixed, heated to 150° C. under nitrogen protection, reacted for 10 hours, cooled to room temperature, filtered, and dried at 80° C. for 24 hours to obtain modified graphene;

[0034] (3) triethoxysilyl undecanealdehyde, dodecyltrimethoxysilane, modified graphene, anhydrous ethanol, and deionized water were mixed in a mass ratio of 1:1.0:0.1:10:3, stirred at 100 rpm for 12 min, adjusted the pH value to 8 with ammonia water, continued stirring for 4 h, and allowed to stand for 12 h to obtain a wet gel;

[0035] (4) The magnesium alloy is placed in the wet gel, pulled up at a speed of 1 cm / min, and then immersed in ethanol for 24 hours. The alloy is taken out and dried at 100° C. for 2 to 3 hours. The above steps are repeated three times to obtain a self-repairing corrosion-resistant coating.

[0036] Comparative Example 1

[0037] The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: 10 parts by mass of D-cystine, 6 parts by mass of graphene oxide, 0.01 parts by mass of methanesulfonic acid, and 25 parts by mass of N,N-dimethylformamide are mixed, heated to 135° C. under nitrogen protection, reacted for 7 hours, cooled to room temperature, filtered, and dried at 80° C. for 24 hours to obtain modified graphene; the remaining steps are the same as in Example 2.

[0038] Comparative Example 2

[0039] The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (3) is changed to: triethoxysilyl undecanealdehyde, dodecyltrimethoxysilane, pretreated graphene, anhydrous ethanol, and deionized water are mixed in a mass ratio of 1:0.7:0.08:8:2, stirred at 100 rpm for 10 min, adjusted to pH 8 with ammonia water, continued stirring for 3 h, and allowed to stand for 10 h to obtain a wet gel; the remaining steps are the same as in Example 2.

[0040] Effect example

[0041] Table 1 below shows the performance analysis results of the coatings of Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.

[0042] Table 1

[0043]

[0044] The present invention utilizes the silicon oxygen bond of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide to be grafted on the graphene surface, and then esterifies it through D-cystine to introduce disulfide bonds to form self-repairing graphene, thereby indirectly improving the self-repairing effect of the coating; then triethoxysilyl undecanealdehyde and dodecyltrimethoxysilane are hydrolyzed and polymerized to form a nano-silica polymer gel, and the aldehyde group of the side chain is chemically bonded with the amino group of the self-repairing graphene to increase the crosslinking density, play a role in sealing the micropores and defects in the coating, and improve the coating. The gel has good corrosion resistance and then relies on its own viscosity to bond to the alloy surface. The amide and disulfide bonds in the gel molecular chain structure contain nitrogen, oxygen, sulfur and other electronegative atoms. They contain lone pairs of electrons and can form coordination bonds to the alloy surface for adsorption. They can better combine with the alloy surface to maximize the corrosion resistance and self-healing properties of the coating, greatly extending the service life of the coating and reducing maintenance costs. At the same time, the long hydrophobic chains carried by the silicone gel can isolate the penetration of corrosive liquids to a certain extent, thereby enhancing the corrosion resistance of the coating.

[0045] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a self-repairing corrosion-resistant coating, characterized in that: The method comprises the following preparation steps: (1) adjusting the pH of the graphene dispersion to 2-5 with hydrochloric acid, adding a coupling agent solution, ultrasonically reacting at 60° C. for 8-20 h, filtering, taking out the solid, repeatedly washing with deionized water until the pH value is neutral, and then drying at 80° C. for 24 h to obtain pretreated graphene; (2) mixing 10 parts by weight of D-cystine, 4 to 7 parts by weight of pretreated graphene, 0.01 to 0.05 parts by weight of methanesulfonic acid, and 20 to 30 parts by weight of N,N-dimethylformamide, heating the mixture under nitrogen protection for reaction, then cooling the mixture to room temperature, filtering the filtrate, and drying the mixture to obtain modified graphene; (3) triethoxysilyl undecylaldehyde, dodecyltrimethoxysilane, modified graphene, anhydrous ethanol, and deionized water were mixed, stirred at 100 rpm for 8 to 12 minutes, the pH value was adjusted to 8 with ammonia water, the stirring was continued for 3 to 4 hours, and the mixture was allowed to stand for 8 to 12 hours to obtain a wet gel; (4) The magnesium alloy is placed in the wet gel, pulled, and then immersed in ethanol for 24 hours, taken out, and dried at 100° C. for 2 to 3 hours. The above steps are repeated 2 to 3 times to obtain a self-repairing corrosion-resistant coating.

2. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: The concentration of the graphene dispersion in step (1) is 1 to 4 wt%.

3. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: The volume ratio of the graphene dispersion to the coupling agent solution in step (1) is 90-99:1-10.

4. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: The volume ratio of N-(3-triethoxysilylpropyl)-4-hydroxybutyramide, anhydrous ethanol and deionized water in the coupling agent solution of step (1) is 15-30:40-70:15-30.

5. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: The ultrasound in step (1) is 20 to 35 kHz.

6. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: The heating reaction in step (2): the reaction temperature is 120-150° C. and the reaction time is 7-10 h.

7. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: The drying step (2) is carried out at a temperature of 80° C. and for 24 hours.

8. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: In step (3), the mass ratio of triethoxysilyl undecanealdehyde, dodecyltrimethoxysilane, modified graphene, anhydrous ethanol and deionized water is 1:0.5-1.0:0.05-0.1:6-10:1-3.

9. The method for preparing a self-repairing corrosion-resistant coating according to claim 1, characterized in that: The pulling speed in step (4) is 1 cm / min.

Citation Information

Patent Citations

  • Method for preparing magnesium alloy surface super-hydrophobic anticorrosion functional film

    CN101934268A

  • Amino stoving varnish composition with scratch self-remediation function and preparation method of amino stoving varnish composition

    CN104610868A

  • Magnesium alloy surface functional graphene coating and preparing method thereof

    CN106048593A

  • Moisture-resistant and corrosion-resistant coating for PTC ceramic heater and preparation method of moisture-resistant and corrosion-resistant coating

    CN116102910A

  • Toughened glass with protection function and production process thereof

    CN117430344A